Exploring the Effect of V2O5 and Nb2O5 Content on the Structural, Thermal, and Electrical Characteristics of Sodium Phosphate Glasses and Glass-Ceramics - Marijan, Sara; Klaser, Teodoro; Mirosavljević, Marija; Mošner, Petr; Koudelka, Ladislav; Skoko, Željko; Pisk, Jana; Pavić, Luka (International journal of molecular sciences, 2024)
Na-V-P-Nb-based materials have gained substantial recognition as cathode materials in high-rate sodium-ion batteries due to their unique properties and compositions, comprising both alkali and transition metal ions, which allow them to exhibit a mixed ionic-polaronic conduction mechanism. In this study, the impact of introducing two transition metal oxides, V2O5 and Nb2O5, on the thermal, (micro)structural, and electrical properties of the 35Na2O-25V2O5-(40 - x)P2O5 - xNb2O5 system is examined. The starting glass shows the highest values of DC conductivity, σDC, reaching 1.45 × 10-8 Ω-1 cm-1 at 303 K, along with a glass transition temperature, Tg, of 371 °C. The incorporation of Nb2O5 influences both σDC and Tg, resulting in non-linear trends, with the lowest values observed for the glass with x = 20 mol%. Electron paramagnetic resonance measurements and vibrational spectroscopy results suggest that the observed non-monotonic trend in σDC arises from a diminishing contribution of polaronic conductivity due to the decrease in the relative number of V4+ ions and the introduction of Nb2O5, which disrupts the predominantly mixed vanadate-phosphate network within the starting glasses, consequently impeding polaronic transport. The mechanism of electrical transport is investigated using the model-free Summerfield scaling procedure, revealing the presence of mixed ionic-polaronic conductivity in glasses where x < 10 mol%, whereas for x ≥ 10 mol%, the ionic conductivity mechanism becomes prominent. To assess the impact of the V2O5 content on the electrical transport mechanism, a comparative analysis of two analogue series with varying V2O5 content (10 and 25 mol%) is conducted to evaluate the extent of its polaronic contribution.
Keywords: Glass; Sodium; niob; PXRD; (micro)structure–property relationship; Ceramics; phosphate glass–ceramics; Niobium; impedance spectroscopy; Electron Spin Resonance Spectroscopy; Phosphates; keramika; sodík; EPR; sklo; ionty; vibrational spectroscopy; Ions; SEM-EDS; elektronová paramagnetická rezonance; electrical properties; fosfáty; phosphate glasses